What drives the business cycle in a small open economy? Evidence from an estimated DSGE Model of the Danish economy - Jesper Pedersen; Søren Hove Ravn (Danmarks Nationalbank, 2013)
Estimated DSGE models have become the standard workhorse model for empirically based macroeconomic analysis in recent years. In this paper, we present an estimated DSGE model for Denmark. The model has been estimated using Bayesian methods and a dataset consisting of 23 macroeconomic variables. We use the model to identify the most important determinants of business cycle fluctuations in Denmark. Our results indicate that foreign shocks explain more than 50 pct. of the variation in Danish real GDP. As an example, the recession that hit Denmark in the wake of the recent financial crisis was to a large extent caused by foreign factors. Shocks originating abroad also played an important role in the build-up to the crisis. However, domestic factors also contributed substantially to the boom in Danish GDP in the years before the crisis, while fiscal policy was not sufficiently contractionary during the boom.
Keywords: C11; E17; E27; E32; 330; DSGE Models; Small Open Economies; Bayesian Estimation